Spectrophotometric Determination of Drotavarine - Begum, Jameelunnisa; Rasheed, Abdul (Asian Journal of Chemistry, 2010)
Three simple sensitive and reproducible visible spectrophotometric methods (A-C) for the determination of drotaverine in bulk samples and pharmaceutical formulations are described. Method A is based on the formation of coloured species with chloranil and acetaldehyde (TQ-acetaldehyde). Method B involves the complex formation between drotavarine and sodium nitroprusside in alkaline medium. Method C is based on the formation of coloured coordination complex with cobalt thiocyanate (CTC). Regression analysis of Beer's law plots showed good concentration ranges 10-50, 4-20 and 10-30 μg/mL for methods, A, B and C, respectively. The applicability of the methods were examined by analyzing tablets or syrup of drotaverine.